COVID-19 disruption to cervical cancer screening in England. (September 2022) - Castanon, Alejandra; Rebolj, Matejka; Pesola, Francesca; Pearmain, Philippa; Stubbs, Ruth
Introduction: In England, routine invitations for cervical screening were reduced between April 2020 and June 2020 due to the COVID-19 pandemic. We quantify the impact of COVID-19 disruptions on attendance and excess diagnoses of cervical cancer (CC). Methods: Using Public Health England CC screening data on laboratory samples received in 2018 as a baseline we quantify the reduction in screening attendances due to the COVID-19 pandemic between April 2020 and March 2021 for women aged 25–64. We model the impact on excess CC diagnoses assuming once invitations resume 87.5% of women attend within 12 months and 12.5% delay screening for 3 or 5 years (depending on age). Results: The number of samples received at laboratories was 91% lower than expected during April, 85% during May and 43% during June 2020 compared to the same period in 2018. Although on average laboratories received 12.6% more samples between August 2020 and April 2021 than over the same months in 2018, by April 2021 there was a short fall of 200, 949 samples (6.4% fewer than in 2018). An excess of 41 CC (4.0 per 100, 000 women with a maximum screening delay of 12 months) are predicted to occur among the estimated 1, 024, 794 women attending this screening round with a delay. An excess of 60 CC (41.0 per 100, 000 women) are predicted to occur among the estimated 146, 391 women who do not attend this screening round. Conclusion: Prompt restoration of cervical screening services limited the impact on excess CC diagnoses. However, in 2020 a 6.4% shortfall of screening samples was observed. Every effort should be made to reassure these women that services are open and safe to attend.